1998
DOI: 10.1210/jcem.83.8.5028
|View full text |Cite
|
Sign up to set email alerts
|

Z−2 Microsatellite Allele Is Linked to Increased Expression of the Aldose Reductase Gene in Diabetic Nephropathy1

Abstract: Epidemiological studies support the hypothesis that genetic factors modulate the risk for diabetic nephropathy (DN). Aldose reductase (ALDR1), the rate-limiting enzyme in the polyol pathway, is a potential candidate gene. The present study explores the hypothesis that polymorphisms of the (A-C)n dinucleotide repeat sequence, located 2.1 kb upstream of the transcription start site, modulate ALDR1 gene expression and the risk for DN. We conducted studies at two different institutions, the University of New Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the present study, the highest level of hexosamines was observed in the model group. On the other hand, long‐term hyperglycemia would activate the aldose reductase (AR), resulting in the accumulation of sorbitol, insufficiency of NADPH and intracellular inositol and enhanced oxidative stress in kidney cells . In the present study, activated polyol metabolic pathway was observed in the model group, which accompanied with a higher concentration of pentoses, lower levels of inositol (Figure H), and glucomannan treatment improved the metabolic pathway by modification of alcohols and inositol profile.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, the highest level of hexosamines was observed in the model group. On the other hand, long‐term hyperglycemia would activate the aldose reductase (AR), resulting in the accumulation of sorbitol, insufficiency of NADPH and intracellular inositol and enhanced oxidative stress in kidney cells . In the present study, activated polyol metabolic pathway was observed in the model group, which accompanied with a higher concentration of pentoses, lower levels of inositol (Figure H), and glucomannan treatment improved the metabolic pathway by modification of alcohols and inositol profile.…”
Section: Discussionmentioning
confidence: 53%
“…An (AC)n microsatellite polymorphism, located 2.1 kb upstream of AKR1B1, was initially reported to be associated with early onset retinopathy in Chinese type 2 diabetic patients [80]. Subsequent studies investigating whether this marker is associated with DN have yielded mixed results [79,[81][82][83][84][85][86][87][88]. NeatmatAllah et al undertook a small meta-analysis of the ( A C ) n marker and found no evidence for an association between the putative Z-2 allele and DN in five studies on type 2 diabetic patients [87].…”
Section: Aldose Reductasementioning
confidence: 99%
“…Recently these studies have been extended to include expression of the ALR2 gene. Patients with T1DM and nephropathy have been found to have three fold higher ALR2 mRNA levels compared to those without nephropathy or non-diabetic renal disease and using highly sensitive ribonuclease protection assays (RPA) this increase was found to be closely linked with the Z-2 5'ALR2 allele [103,104]. Patients with at least one copy of the Z-2 allele had more than two fold higher levels of ALR2 mRNA compared to those without.…”
Section: Alr2 Polymorphisms and Gene Expressionmentioning
confidence: 99%